Practical junk rig : design, aerodynamics and handling - Hasler, Herbert George, 1914-1987 (Adlard Coles Nautical, 2004)
This encyclopaedic volume synthesises 25 years of research and development of this unique rig as adapted to western craft. It is a work which has been welcomed by the growing number of yachtsmen and designers throughout the world who already enjoy the benefits of junk rig or who wish to do so. Now in paperback for the first time, Practical Junk Rig examines the design and aerodynamic theory behind junk rigs and discusses how best to sail them . It outlines the rig in detail, the principles that underlie it, considers possible alternative shapes and arrangements and analyses performance, all as.